Dramaterapia: Aproximación a la construcción de sentidos de vida en jóvenes universitarios - Pineda Cárdenas, Juliana (2024)
What is it like to live without questioning the meaning of existence? This document proposes how something as common and chaotic as existential crises can find transformation and change through drama therapy. This therapeutic tool facilitates emotional expression through drama (acting, play, dramaturgy, masks, among other elements of theatrical art) and generates powerful introspection processes in participants through their self-awareness, through provocative questions posed by the drama therapist. The social symptoms of existential emptiness end up generating emotional difficulties that can even lead to the loss of life for those who experience them. For this reason, it is decided to work with young people, as they are the population most affected by this problem. In other words, drama therapy aims to propose a path that approaches the construction of the purpose for which young people want to guide their lives. It is mixed research with a phenomenological and quasi-experimental design of pretest-post-test using the Purpose In Life (PIL) instrument, developing nine drama therapy workshops as an intervention strategy with nine university students. The average scores of the pretest (91.8, 104, 120) increased after the workshops (111.4, 118, 123.50). The effectiveness of drama therapy is supported by multiple variables (teamwork, collective support, love, and the possibility of observation from the outside). Drama therapy as an intervention strategy is a different, little-researched, and innovative way of working on an emotional level, as it provides the possibility of taking action in the face of one’s destiny and the way of seeing and acting in life.